2022
DOI: 10.3390/jof8030262
|View full text |Cite
|
Sign up to set email alerts
|

Myco-Synthesized Molluscicidal and Larvicidal Selenium Nanoparticles: A New Strategy to Control Biomphalaria alexandrina Snails and Larvae of Schistosoma mansoni with an In Silico Study on Induced Oxidative Stress

Abstract: Schistosomiasis is a tropical disease with socioeconomic problems. The goal of this study was to determine the influence of myco-synthesized nano-selenium (SeNPs) as a molluscicide on Biomphlaria alexandrina snails, with the goal of reducing disease spread via non-toxic routes. In this study, Penicillium chrysogenum culture filtrate metabolites were used as a reductant for selenium ions to form nano-selenium. The SeNPs were characterized via UV-Vis spectrophotometer, Fourier transform infrared (FT-IR) spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 76 publications
5
29
0
Order By: Relevance
“…Thus, we can suggest that the various rates of DNA damage seen with our preparations may be corroborating oxidative stress, which in an uncontrolled way results in a breakdown of the DNA tape [ 35 , 60 ]. Studies also reported an increase in DNA damage rates in groups treated with household slat [ 61 ], sodium selenium [ 62 ] and aqueous extract of Anagallis arvensis [ 63 ], which corroborates our results.…”
Section: Resultssupporting
confidence: 91%
“…Thus, we can suggest that the various rates of DNA damage seen with our preparations may be corroborating oxidative stress, which in an uncontrolled way results in a breakdown of the DNA tape [ 35 , 60 ]. Studies also reported an increase in DNA damage rates in groups treated with household slat [ 61 ], sodium selenium [ 62 ] and aqueous extract of Anagallis arvensis [ 63 ], which corroborates our results.…”
Section: Resultssupporting
confidence: 91%
“…Powder X-ray diffraction (XRD) pattern analysis demonstrated a broad pattern analogous to [ 6 ]. XRD did not confirm crystallinity of the myco-synthesized SeNPs, or, to be more precise, of the selenium phase in the compositions under question because of this method’s inability to distinguish between different the oxidation states of selenium.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to a broad set of applications of nanoparticles (NPs), fungal-assisted fabrication of nanomaterials has attracted the attention of scientists to a novel area of research, myco-nanotechnology [ 4 ], a new term that was proposed originally by Mahendra Rai et al [ 5 ]. Commercially versatile, highly metal tolerant, easy to handle, with large biomass and metabolite yield, mushroom cultures are well suited for the production of a wide range of nanoparticle types [ 6 ], including selenium NPs (SeNPs). Selenium is an essential nutrient that regulates a variety of cellular processes in every living organism [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, monodispersed selenium nanospheres with an average size of 24.65 nm exhibiting antibacterial activity were obtained using P. chrysogenum culture liquid and Na 2 SeO 3 as a precursor [ 212 ]. Other researchers obtained molluscicidal and larvicidal SeNPs (44–78 nm) using a P. chrysogenum culture liquid [ 213 ]. El-Sayyad et al developed a method to produce nanoparticles involving the incubation of a P. chrysogenum filtrate with Na 2 SeO 4 following the application of gamma irradiation [ 214 ].…”
Section: Fungi-mediated Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…Of great interest is the use of medicinal fungi to produce nanoparticles with complex medical activity, which is achieved by combining the properties of the nanoparticles themselves and of the fungal metabolites acting as capping agents [ 169 ]. Activity of the nanoparticles against insect larvae and pupae spreading human diseases [ 53 , 216 , 244 , 245 , 246 ], as well as against pathogen vector mollusks [ 213 , 247 ], is also of interest in terms of the use of mycogenic AuNPs, AgNPs and SeNPs as an eco-friendly and cost-effective tool for disease biological control. Mycosynthesized nanoparticles have great potential for use as carriers in targeted drug delivery, for bioimaging and biolabeling, as sensors for optical and electronic devices and in the cosmetics, textile and food processing industries [ 240 , 248 , 249 ].…”
Section: Advantages Of Fungi-mediated Nanoparticle Synthesis and Pros...mentioning
confidence: 99%